PENGARUH MEDIA BLOK PECAHAN TERHADAP PEMAHAMAN KONSEP PERBANDINGAN PECAHAN SISWA KELAS V SDN 2 BAJUR TAHUN AJARAN 2024/2025 - Azanda, Ismi; Ermiana, Ida; Rachmatul Hidayati, Vivi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of using fraction block media on fifth-grade students' understanding of fraction comparison concepts at SDN 2 Bajur. The research employed a quasi-experimental method with a nonequivalent control group design. The sample consisted of 50 students, with Class VA (25 students) as the experimental group and Class VB (25 students) as the control group. Data were collected using tests. The analysis results showed an improvement in understanding after the treatment. The average post-test score of the experimental group was 84.40, while the control group scored an average of 76.80. The hypothesis test using an independent sample t-test showed a significance value (2-tailed) of 0.033 ≤ 0.05, indicating that H₀ was rejected and Hₐ was accepted. This suggests a significant effect of using fraction block media on students’ understanding of fraction comparison concepts. The effectiveness of the media was calculated at 67.30%, categorized as moderately effective. Therefore, the use of fraction block media has proven effective in enhancing fifth-grade students' understanding of fraction comparison concepts at SDN 2 Bajur.